The textual basis of English translations of the Hebrew Bible - Daley, S. C. (Supplements to the textual history of the Bible, 2019)
S.C. Daley's book, The Textual Basis of English Translations of the Hebrew Bible, moves us beyond existing uncertainties about the textual basis of modern Bible translations to a fresh understanding of the text-critical constitution of well-known English translations of the past four hundred years. Most translations depart from the Masoretic Text selectively, and in-depth analysis of their textual decisions leads (1) to the identification of distinct periods in the textual history of the English Bible, (2) to a classification of the translations by eclectic type, and (3) to the observation that each translation is ultimately unique from a text-critical perspective. The study then revisits the topic of the text to be translated in Bibles intended for the wider public.